Restoration of Olfactory Memory in Drosophila Overexpressing Human Alzheimer’s Disease Associated Tau by Manipulation of L-Type Ca2+ Channels - Higham, James P.; Hidalgo, Sergio; Buhl, Edgar; Hodge, James J. L. (Frontiers in Cellular Neuroscience, 2019)
The cellular underpinnings of memory deficits in Alzheimer’s disease (AD) are poorly understood. We utilized the tractable neural circuits sub-serving memory in Drosophila to investigate the role of impaired Ca2+ handling in memory deficits caused by expression of human 0N4R isoform of tau which is associated with AD. Expression of tau in mushroom body neuropils, or a subset of mushroom body output neurons, led to impaired memory. By using the Ca2+ reporter GCaMP6f, we observed changes in Ca2+ signaling when tau was expressed in these neurons, an effect that could be blocked by the L-type Ca2+ channel antagonist nimodipine or reversed by RNAi knock-down of the L-type channel gene. The L-type Ca2+ channel itself is required for memory formation, however, RNAi knock-down of the L-type Ca2+ channel in neurons overexpressing human tau resulted in flies whose memory is restored to levels equivalent to wild-type. Expression data suggest that Drosophila L-type Ca2+ channel mRNA levels are increased upon tau expression in neurons, thus contributing to the effects observed on memory and intracellular Ca2+ homeostasis. Together, our Ca2+ imaging and memory experiments suggest that expression of the 0N4R isoform of human tau increases the number of L-type Ca2+ channels in the membrane resulting in changes in neuronal excitability that can be ameliorated by RNAi knockdown or pharmacological blockade of L-type Ca2+ channels. This highlights a role for L-type Ca2+ channels in tauopathy and their potential as a therapeutic target for AD.